In vitro knockdown of TsDNase II-7 suppresses Trichinella spiralis invasion into the host's intestinal epithelial cells. - Jing Wang; Xuemin Jin; Chengyao Li; Xinhui Chen; Yanfeng Li; Mingyuan Liu; Xiaolei Liu; Jing Ding (Public Library of Science (PLoS), 2023)
Trichinella spiralis (T. spiralis) adult-specific deoxyribonuclease II-7 (TsDNase II-7), a member of the DNase II-like nuclease family with no DNase II activity, was identified in the excretory-secretory (ES) products of adult worms (AWs). However, its biological functions are still unclear. Our previous study revealed that TsDNase II-7 is located around the infection site in the intestinal tissue, speculating that it was involved in the T. spiralis invasion of host intestinal epithelial cells (IECs). This study aimed to use RNA interference to verify our speculation that TsDNase II-7 in 3-day old adult T. spiralis (Ad3) plays a role in intestinal invasion. TsDNase II-7-specific small interfering RNAs (siRNAs) were delivered into muscle larvae (MLs) to knockdown TsDNase II-7 expression by electroporation. Twenty-four hours later, the MLs transfected with 2 μM siRNA-841 exhibited decreased in TsDNase II-7 transcription and expression as compared to the control MLs. The knockdown of TsDNase II-7 expression did not affect ML viability, and the low expression of TsDNase II-7 still maintained in Ad3 recovered from TsDNase II-7-RNAi-ML infected mice, resulting in a weakened ability of Ad3 to invade intestinal epithelial cells (IECs). These results indicated that knockdown of TsDNase II-7 gene expression via RNA interference (RNAi) suppressed adult worm invasion and confirmed that TsDNase II-7 plays a crucial role during the intestinal phase of T. spiralis infections, which provided new candidate for vaccine development of T. spiralis.